PENGARUH INTENSITAS MODAL, PERTUMBUHAN PENJUALAN DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK - Desviya Marta; Nofryanti Nofryanti (Faculty of Economics and Business, 2023)
This study aims to determine the effect of capital intensity, sales growth and company size on tax avoidance in healthcare companies listed on the indonesia stock exchange. This type of research is type of quantitative research. The data used in this study is secondary from the indonesia stock exchange for the period 2016-2020. The number of samples in this study were 8 companies with an observation period of 5 years so that the number of research samples is 40.. The technic used in this research is purposive sampling. The data in this study used panel data regression analysis using the Eviews 12 application. Based on the results of panel data regression analysis, it show that capital intensity have no effect on tax avoidance, sales growth and company size an effect on tax avoidance.